Nilai-Nilai Antikorupsi Pada Masyarakat Sedulur Sikep Di Sukolilo Pati - Falasifatul Falah; Zamroni Zamroni (Universitas Islam Indonesia, 2016)
Corruption has become a serious problem in Indonesia because it spreads across all sectors and sectors in a widespread, systematic, and well organized society. Corrupt behavior as if entrusted in all levels of society, from the top to the grassroots level. Indonesian people need to learn about the anti-corruption values of Sedulur Sikep (Samin) society. This study aims to determine the extent to which Sedulur Sikep people know about the phenomenon of corruption that occurred in Indonesia, the anti-corruption values that underlie their way of life, how their attitude toward corruption, and what they do when facing corrupt behaviors that entrapment in Indonesia. Honesty and independence are the most important foundation for Sedulur Sikep society so that the appeal of these values is consistent with their daily attitude of life.